Is luck capabilitarianism possible? - Garcia Valverde, Facundo (2018)
Capability theorists claim that real freedoms should constitute the informational basis for assessing individual wellbeing. Nevertheless, they have not yet developed a normative theory of social justice accounting for why or under what circumstances a political community has the obligation to mitigate deficits in real freedoms. This paper examines whether combining Luck Egalitarianism principles with capabilities as a metric of advantage can deliver an acceptable solution to this problem. However, in light of its inconsistency with the core claims found in capability literature, this paper ultimately rejects that possibility for two reasons: First, because it disregards the multidimensional character of the metric. Second, because it undermines the notion that capabilities are valuable not just because they represent positive freedom but because of the beings and doings they enable.